Proton can compete globally with foreign strategic partner - Daily Express, (KK) (Daily Express, 2017)
KUALA LUMPUR: The impending collaboration between national car company, Proton, and a foreign strategic partner (FSP) will not only maximise the manufacturing capacity at both its Shah Alam and Tanjung Malim plants but also allow the company to compete effectively, regionally and globally.